Zadłużenie miast na prawach powiatu - wybrane problemy - Babczuk, Arkadiusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The subject of the following study is debt of great polish cities. They are the most indebted polish municipalities. They use special kind of financial instruments to manage their debt. Municipal bonds are significant part of great cities debt.The most significant factor that have influenced the level of the great polish cities debt is population. The biggest cities have the biggest financial needs and credibility. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 480-489